Ekstraksi Litium dari β – Spodumen Hasil Dekomposisi Batuan Sekismika Indonesia Menggunakan Aditif Natrium Sulfat [Lithium Extraction from β-Spodumene the Decomposition Product of Schist Mica Indonesia Using Sodium Sulphate as Additive] - Natasha, Nadia Chrisayu; Lalasari, Latifa Hanum; Rohmah, Miftakhur; Sudarsono, Johny Wahyuadi (Jurnal Metalurgi, 2018)
Spodumene is one of minerals that present in hard rock as lithium resources. Mineral for lithium resources in nature is α-phase spodumene. Requirement of lithium extraction from spodumene by leaching is the presence of β-form phase in ore because it has a porosity that makes it more reactive than α-form. Formation of β-phase spodumene was obtained from schist mica Kebumen, Center Java, Indonesia by roasting method using sodium sulfate at 650, 700, 750 and 800 oC for 20, 40 and 60 minutes. Leaching was done to determine the phase effect on lithium extraction percentage. The variations of solid and liquid ratio on this leaching are 1 : 15, 1 : 10, 1 : 5, 1 : 2 and 1 : 1 (g/mL). Leaching was done using aquadest for 1 h. STA (simultaneous thermal analysis) was used to determine reaction temperature between schist mica and sodium sulfate by thermal treatment. XRD (x-ray diffraction) and SEM (scanning electron microscopy) were used to examine the presence of spodumene phase, morphology and particle size. While the composition of schist mica was determined by ICP (inductively coupled plasma). In schist mica from Kebumen, Center Java, Indonesia indicates that spodumene exist in it. β-phase spodumene started to form at 700 oC for 20 minutes and it phase changed at 750 oC for 40 minutes become sanidine (AlLiO8Si3). Optimum value of extraction percentage from this investigation is 70.6% at 700 oC for 40 minutes.